Preparation of silica/poly(styrene‐co‐butyl acrylate) core/shell composite particles for absorption of toluene. Issue 16 (5th January 2018) - Dong, Xiaojie; Li, Xiao; Xie, Zhenpeng; Weng, Sen; Zhang, Weiying; Ying, Xiaoguang
ABSTRACT: An absorbent for benzene series with silica/poly(styrene‐ co ‐butyl acrylate) core/shell structure was prepared via emulsion polymerization. The effects of emulsifier dosage, monomer concentration, and crosslinker dosage on the absorption of the core/shell composite particles were investigated. The composite particles with good absorbency could be obtained when the emulsifier concentration was 2.5 g/L, monomer concentration was 40 g/L, crosslinker dosage was 2.0% (based on the total mass of the monomer), and the initiator dosage was 1.0%. The composite particles exhibited a rapid absorption and the absorption process conformed to the quasi‐second order kinetics. Fourier‐transform infrared spectroscopy, scanning electron microscope, and energy dispersive spectrometer (EDS) showed the presence of copolymer layer on the surface of silica. The work provided a new path to fabricate novel composite absorbent particles for a wide range of applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46172. Abstract :